3D amperometry in the liquid chromatographic determination of trace pharmaceutical and herbicide emerging compounds. Issue 12 (26th September 2018) - Rivoira, Luca; Castiglioni, Michele; Del Bubba, Massimo; Bruzzoniti, Maria Concetta
ABSTRACT: In this work, we innovatively applied the 3D amperometry detection, coupled to liquid chromatography, for the determination of a mixture of chromatographically unresolved compounds (two herbicides—monuron and bentazon, one drug—propranolol and the main metabolite of an antiepileptic drug—5-(4ʹ-hydroxyphenyl)-5-phenylhydantoin). Exploiting the post-chromatographic current integration, a scanning waveform was successfully applied to explore a wide range of potentials (0.0–1.3 V) to find the peculiar oxidative potential value for each compound. This approach allowed us to obtain 3D chromatograms (elution time vs potential vs current) in which coeluted species could be clearly distinguished. Quantitation was easily obtained by extraction of 2D chromatograms (elution time vs integrated current), from the 3D ones, at the optimised waveform time ranges (800–1, 000 msec and 1, 500–1, 700 msec, corresponding to 0.6–0.8 V and 1.0–1.2, respectively). Validation of the proposed 3D amperometry method was performed in terms of linearity, limits of detection and quantitation and repeatability. Matrix effect was studied by statistical treatment on a wastewater effluent. By coupling an on-line solid phase extraction step prior to separation and detection by 3D amperometry, detection limits were significantly reduced (57 ng/L for bentazon, with recovery yields of 82.9 ± 10.9%). It is worth mentioning that this value fully satisfies the requirements of the 98/83/CE directive for the determination of bentazon in groundwater.